Teaching English to Young Learners (TEYL) at Elementary School - Hijriati, Sartika (MASALIQ, 2023)
Teaching young learners is quite challenging and teachers need to be creative. This research aims to investigate the material used in English teaching-learning process for young learners in 5th grade 5A and 5B classes and in 6th grade 6A and 6B classes of an Elementary school of SDN 2 Kekeri in West Lombok, West Nusa Tenggara Province. The subjects of the study were a teacher and her students. To find the data in question research, the research used two types of instruments that are checklist observation and score rubric. The result shows there are four materials that most student teachers used to practice reading, writing, listening, and speaking English through games, worksheets, and role-plays, such as slides, songs, photographs, and drawings. It was found that their average score of 88.25 in 5th grade and an average score of 88.36 in 6th grade. Thus, it can be concluded that their English is in very well category.